Quality assurance of development projects in the design, construction and engineering processes: sustainable development, standards and innovative approaches - Tugay, Оleksii; Pokolenko, Vadym; Yesipenko, Alla; Skakun, Volodymyr (Ways to Improve Construction Efficiency, 2025)
The article examines the scientific and methodological principles of ensuring the quality of development projects in the design, construction and engineering processes in the context of implementing the concept of sustainable development. The relevance of the study is due to the increasing complexity of development activities, the increasing requirements of investors and society for the environmental, social and economic performance of construction projects, as well as the need to integrate international standards and innovative approaches into the quality management system. It is substantiated that traditional fragmentary approaches to quality assurance do not ensure the achievement of long-term value of development projects and require a systematic review.The aim of the article is to scientifically substantiate an integrated approach to ensuring the quality of development projects, which combines the principles of sustainable development, standardization and modern innovative management tools. The study used methods of system analysis, generalization and logical modeling, which allowed to reveal the role of standards and certification systems at different stages of the project life cycle. It is proven that standards perform a system-forming function, ensuring the manageability and reproducibility of processes, while certification systems for sustainable construction carry out independent verification of results and transform the internal quality of management into an externally recognized investment characteristic. The article proposes a conceptual model “standards - certification systems - investment value”, which reflects the logic of the transition from the normatively ensured quality of processes to increasing the investment attractiveness of development projects. Based on the analysis of practice, the most common certification systems in Ukraine (BREEAM, LEED, EDGE) were identified and their impact on reducing risks, increasing liquidity and long-term capitalization of real estate objects was substantiated. The results of the study can be used to improve quality management systems for development projects, forming investment-attractive solutions and further scientific research in the field of development and sustainable development.